Transplante multivisceral em suínos: modelo de pesquisa e treinamento - David, Andre Ibrahim; Chida, Valeria Vieira; Lee, Andre Dong Won; Fiuza, Felipe Soares Oliveira Rodrigues; Calil, Daniela Medeiros; Mantovani, Danielle de Carvalho; Maranhão, Eduardo Rullo; Campi, Gabriel Beligni; Llanos, Juan Carlos [UNESP]; Ferraz Neto, Jose Ben Hur (FapUNIFESP (SciELO), 2011)
Objective: To present a model for research and training in multivisceral transplantation in pigs. Methods: Eight Large White pigs (four donors and four recipients) were operated. The multivisceral transplant with stomach, duodenum, pancreas, liver and intestine was performed similarly to transplantation in humans with a few differences, described below. Anastomoses were performed as follows: end-to-end from the supra-hepatic vena cava of the graft to the recipient juxta diaphragmatic vena cava; end-to-end from the infra-hepatic vena cava of the graft to the inferior (suprarenal) vena cava of the recipient; and endto-side patch of the aorta of the graft to the infrarenal aorta of the recipient plus digestive reconstruction. Results: The performance of the multivisceral transplantion was possible in all four animals. Reperfusions of the multivisceral graft led to a severe ischemia-reperfusion syndrome, despite flushing of the graft. The animals presented with hypotension and the need for high doses of vasoactive drugs, and all of them were sacrificed after discontinuing these drugs. Conclusion: Some alternatives to minimize the ischemia-reperfusion syndrome, such as the use of another vasoactive drug, use of a third pig merely for blood transfusion, presence of an anesthesia team in the operating room, and reduction of the graft, will be the next steps to enable experimental studies.

Objetivo: Apresentar um modelo de pesquisa e treinamento em transplante multivisceral em suínos. Métodos: Oito porcos da raça Large White (quatro doadores e quatro receptores) foram operados. O transplante multivisceral com estômago, duodeno, pâncreas, fígado e intestino foi realizado a semelhança do transplante em seres humanos com algumas diferenças descritas a seguir. Foram realizadas as anastomoses de veia cava supra-hepática do enxerto com a veia cava do receptor justa diafragmática término-terminal, veia cava infrahepática do enxerto com a veia cava inferior (suprarrenal) do receptor término-terminal e patch da aorta do enxerto com a aorta infrarrenal do receptor término-lateral e reconstrução digestiva. Resultados: Foi possível a realização do transplante multivisceral nos quatro animais. A reperfusão do enxerto multivisceral levou a uma grave síndrome de isquemia-reperfusão, apesar do flushdo enxerto. Os animais apresentaram hipotensão com necessidade de drogas vasoativas em altas doses, sendo todos sacrificados com a retirada dessas drogas. Conclusão: Alternativas para minimizar a síndrome de isquemiareperfusão, como o uso de mais de uma droga vasoativa, uso de um terceiro porco apenas para transfusão sanguínea, presença de uma equipe de anestesia na sala de cirurgia e redução do enxerto, serão os próximos passos para possibilitar estudos experimentais.
Multivisceral transplantation in pigs: a model for research and training
Keywords: Transplants/methods; Viscera/transplants; Animal models; Professional training; Swine; Transplantes/métodos; Vísceras/transplante; Modelos animais; Capacitação profissional; Suínos